Religious life of Ukraine in 1998 in figures - Anatolii M. Kolodnyi (Українське Pелігієзнавство, 1999)
In 1998, Ukraine continued to characterize complex processes in the field of religious life, interdenominational and inter-church relations. On January 1, 1999, there were 21,018 registered religious organizations, 825 communities declared their existence. Among these community organizations - 2,934, monasteries - 232 with 4609 monks, religious schools - 94 with 13078 listeners, missions - 144, fraternities - 35. Religious organizations had 19312 servicemen (of which 578 were foreigners), 6,400 Sunday schools, 173 periodicals. The official list includes 76 religious movements. If we consider the presence of four Muslim associations and three Jews, we can talk about the activities of 81 organized religious organizations.